The Impact of Public Spending on Kaldor's Square Variables in Iraq for the period (2005-2016). (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The paper aims to measure and analysis the impact Public Spending on Iraq economy (Kaldor Variables). (variables of the magic square Kaldor) and them in after 2003.The paper adopted econometric Methods to test the stationarity of the Variables under consideration. For the period (2005-2016) by using multiple regression and estimation the Impulse response function (IRF), by adopting Eviews 10 program.The results of Impulse response function for the following five-years after the period under consideration reflexes that public expenditure (PEX) was fluctuating between positive and negative in all the variables of the research and this shows the fragility of the performance of fiscal policy in Iraq.The paper recommended that the Iraqi economy should be diversified, activated public and private sectors, real sectors, elimination all the obstacles in front of developing these issues.The paper divided in to two sections. The first deals with theoretical framework and specification econometric model. The second section deals with measurement and analysis the impact of public expenditure on Kaldor's variables (growth rate, unemployment rate, balance of payments, and inflation rate).